2021
DOI: 10.1088/1361-6463/ac1462
|View full text |Cite
|
Sign up to set email alerts
|

Glass/glass photovoltaic module reliability and degradation: a review

Abstract: Glass/glass (G/G) photovoltaic (PV) module construction is quickly rising in popularity due to increased demand for bifacial PV modules, with additional applications for thin-film and building-integrated PV technologies. G/G modules are expected to withstand harsh environmental conditions and extend the installed module lifespan to greater than 30 years compared to conventional glass/backsheet (G/B) modules. With the rapid growth of G/G deployment, understanding the outdoor performance, degradation, and reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 110 publications
2
44
1
Order By: Relevance
“…The two leading choices for bifacial PV packaging are glass/glass (G/G) or glass/transparent backsheet (G/TB) constructions, though it is currently unclear which choice will produce the lowest module degradation rates. 4,5 Scheme 1a highlights several different degradation pathways possible in G/G versus G/TB structures. G/G construction promises greater mechanical rigidity 6,7 and low rates of moisture/ atmospheric ingress, [8][9][10] leading to community recommendations to use G/G in harsh environments and extreme climates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two leading choices for bifacial PV packaging are glass/glass (G/G) or glass/transparent backsheet (G/TB) constructions, though it is currently unclear which choice will produce the lowest module degradation rates. 4,5 Scheme 1a highlights several different degradation pathways possible in G/G versus G/TB structures. G/G construction promises greater mechanical rigidity 6,7 and low rates of moisture/ atmospheric ingress, [8][9][10] leading to community recommendations to use G/G in harsh environments and extreme climates.…”
Section: Introductionmentioning
confidence: 99%
“…4,11 However, older generations of G/G modules containing poly (ethylene-co-vinyl acetate) (EVA) suffered from entrapment of encapsulant degradation products (e.g., acetic acid), historically causing encapsulant discoloration, package delamination, and metallization corrosion. 5,12,13 These degradation modes could be mitigated by using higher quality formulations, different encapsulants that produce less detrimental degradation products (e.g., polyolefins [POE]), or, to some extent, by using TBs that may allow out-diffusion of degradation products. 5 G/TB constructions also promise lower module operating temperatures, 14,15 lower weight (i.e., easier installation), 11 and less susceptibility to some types of potential-induced degradation (PID).…”
Section: Introductionmentioning
confidence: 99%
“…Albadwawi et al [16] found that in extreme desert conditions, the front side discoloration can cause a degradation of 1.3-1.88% per year while for the rear side, this degradation is around 0.39-0.78% per year. Additionally, as BPV modules use common double glass technology, they showed to be more likely to trap acetic acid and gases produced during the degradation of the encapsulant as the glass layer is less breathable than a back sheet [63].…”
Section: Encapsulant Discoloration and Delaminationmentioning
confidence: 99%
“…It is, therefore, clear that one of the requirements is a correspondingly long service life. In addition, it has already been shown in the literature that glass-glass modules have a longer service life than glass-foil modules [10,22,23].…”
Section: Introductionmentioning
confidence: 99%